Où sont les étudiants du supérieur ? Démobilisation et réengagement du milieu universitaire en Turquie et au-delà - Jordi Tejel Gorgas (European Journal of Turkish Studies)
The uprisings that erupted unexpectedly in the Middle East between 2010 and 2011 propelled this region’s youth to the forefront of the political and media scene. To some scholars, we are witnessing a re-politicisation of the Middle Eastern youth, which stands in marked contrast to their "depoliticisation" and "apathy" of recent years. Yet, although the participation of the youth "by the way the ’majority’ of the population in the region" to popular protests is an undeniable fact, student unions seem to be out of the picture so far. From a macro-level perspective, the marginal role of student associations may appear "natural". Whilst nationalist and revolutionary leaders encouraged students to actively participate in politics "for the sake of the nation" until the 1960s, revolutionary as well as conservative regimes progressively sought to "depoliticize" them. In that respect, the university field became a privileged site of experimentation of methods of repression which would then be expanded to be used in all sectors of society. However, though scholars must take into consideration the political context of a given society "authoritarian or semi-authoritarian in most of Middle Eastern countries", what the meso and micro levels of analysis reveal us about the complex and multi-layered phenomena of collective demobilization and individual disengagement? This special issue offers some responses to that central question while analyzing different case studies within the university milieu from Turkey to Egypt, Morocco, and Mexico over the last forty years.